Analisis Kriminal Kejahatan Cyber Extortion Berkedok Love Scamming di Lingkungan Lembaga Pemasyarakatan - Rizky Pratama (Jurnal Hukum Lex Generalis, 2026)
Cyber extortion under the guise of love scamming is a cybercrime that exploits false emotional connections to commit blackmail through electronic media. This study aims to analyze the workings and operational structure of cyber extortion syndicates under the guise of love scamming and the factors that contribute to the circulation of illegal communication devices in correctional institutions. The study used empirical legal methods with a criminological and legislative approach. Data were obtained through interviews and literature review, then analyzed qualitatively. The results indicate that the crime is committed through victimization, establishing emotional relationships, exploiting personal data, extortion, and concealing the proceeds of crime. Contributing factors include overcapacity, limited officers, the involvement of individuals, weak security technology, and external network support.